2011
DOI: 10.1007/s12185-011-0842-7
|View full text |Cite
|
Sign up to set email alerts
|

Case series of pediatric acute leukemia without a peripheral blood abnormality, detected by magnetic resonance imaging

Abstract: Although abnormal peripheral blood counts are a key diagnostic finding for acute leukemia in children, between 2003 and 2010 we observed seven pediatric cases without peripheral blood abnormalities and showing abnormal signals in the bone marrow by magnetic resonance imaging (MRI). The common chief complaint in these patients was bone pain and fever. Bone marrow tests revealed six out of the seven cases to be acute leukemia, whereas one patient was diagnosed with juvenile idiopathic arthritis (JIA). There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 5 publications
(4 reference statements)
2
26
0
2
Order By: Relevance
“…Kato et al . reported the same findings for juvenile idiopathic arthritis as in the present case . They speculate that the bone marrow findings indicate an increase in activated monocytes and macrophages, suggesting high cytokines in juvenile idiopathic arthritis.…”
supporting
confidence: 88%
“…Kato et al . reported the same findings for juvenile idiopathic arthritis as in the present case . They speculate that the bone marrow findings indicate an increase in activated monocytes and macrophages, suggesting high cytokines in juvenile idiopathic arthritis.…”
supporting
confidence: 88%
“…Diagnosis of ALL was based principally on morphological identification of leukemic bone marrow blasts >25%. In some cases, repeated bone marrow examination is required to confirm the diagnosis . Immunophenotype assessment on flow cytometry (FCM) is necessary, and most pediatric ALL cases are clinically classified as B‐cell precursor (BCP), T‐cell ALL, or mature B‐cell types, comprising 80%, 15%, and 5% of cases, respectively.…”
Section: Diagnosis and Treatment Stratificationmentioning
confidence: 99%
“…However, because appropriate chemotherapy for ALL immediately relieves severe musculoskeletal pain caused by ALL, an accurate early diagnosis is beneficial for these patients. As reported by Kato et al [9], MRI can detect changes in the bone marrow infiltrated with leukemic cells at an early phase, but local high signal intensity on T2WI might occasionally lead to misdiagnosis with acute osteomyelitis or arthritis. Bone marrow examination is strongly recommended in addition to invasive procedures such as arthrocentesis to the local lesion with high signal intensity on T2WI, whenever T1WI depicts diffuse low signal intensity of bone marrow.…”
Section: Discussionmentioning
confidence: 98%
“…It is also the best imaging modality that can directly depict the bone marrow condition and marrow infiltration in malignant diseases, including acute leukemia, with high anatomical resolution and excellent soft tissue contrast [7, 8]. Kato et al [9] demonstrated that MRI is useful for diagnosing pediatric acute leukemia presenting with prolonged bone pain and without peripheral blood abnormality. In their report, MRI detected leukemic bone marrow involvement by low signal intensity on T1-weighted magnetic resonance images (T1WI) and high signal intensity on T2-weighted magnetic resonance images (T2WI).…”
Section: Introductionmentioning
confidence: 99%